Peningkatan hasil belajar Pendidikan Kewarganegaraan (PKn) pada peserta didik kelas 3 SDN 02 Talun melalui media CD interaktif - Darsono Darsono (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This study aims to improve the students' story writing skills and increase the Citizenship Education (Civics) as a tool for maturation for students with a conscious and planned effort through learning so that changes occur in these students related to national knowledge, attitudes, and behavior. The purpose of this study was to improve the learning outcomes of Citizenship Education (Civics) in 3rd grade students of SDN 02 Talun through interactive CD media. This type of research is Classroom Action Research (CAR) with four stages, namely planning, action, observation and reflection. In this study, two research cycles were conducted. The subjects in this study were 19 students of SDN 02 Talun, Pekalongan Regency. Data collection techniques in this study are observation, tests, documentation and interviews. The success indicator in this study is for individual learning completeness if the proportion of students' correct answers is more than the predetermined KKM and for classical learning completeness if at least 85% of all students have reached the KKM. The results of this study for the first cycle of classical completeness reached 73.68% with 14 students who reached the KKm. While in cycle 2, classical completeness reached 89.47% with 17 students who reached the KKM. So that in cycle 2 the success indicator is achieved